2015
DOI: 10.1208/s12249-015-0405-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Antidiabetic Activity and Oxidative Stress Induced by Zinc Oxide Nanoparticles and Zinc Sulfate in Diabetic Rats

Abstract: Abstract. In the current study, antidiabetic activity and toxic effects of zinc oxide nanoparticles (ZnO) were investigated in diabetic rats compared to zinc sulfate (ZnSO 4 ) with particular emphasis on oxidative stress parameters. One hundred and twenty male Wistar rats were divided into two healthy and diabetic groups, randomly. Each major group was further subdivided into five subgroups and then orally supplemented with various doses of ZnO (1, 3, and 10 mg/kg) and ZnSO 4 (30 mg/kg) for 56 consecutive days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 60 publications
4
58
0
Order By: Relevance
“…Diabetes mellitus is a serious public health problem, and the WHO has estimated that, in 2014, there were more than 400 million adults with diabetes all over the world [ 99 ]. Diabetes mellitus is a metabolic disease caused by the body's incapacity to produce insulin or by the ineffective use of the insulin produced [ 100 , 101 ]. Zinc is a trace element and abundantly found mineral in all human tissues and tissue fluids.…”
Section: Biomedical Applications Of Zno Nanoparticlesmentioning
confidence: 99%
“…Diabetes mellitus is a serious public health problem, and the WHO has estimated that, in 2014, there were more than 400 million adults with diabetes all over the world [ 99 ]. Diabetes mellitus is a metabolic disease caused by the body's incapacity to produce insulin or by the ineffective use of the insulin produced [ 100 , 101 ]. Zinc is a trace element and abundantly found mineral in all human tissues and tissue fluids.…”
Section: Biomedical Applications Of Zno Nanoparticlesmentioning
confidence: 99%
“…It was observed that those treated with ZnO showed greater antidiabetic activity compared to ZnSO 4 . However, severely elicited oxidative stress particularly at higher doses was also observed [ 112 ]. The efficacy of ZnO QDs in attenuating pancreatic damage in a rat model of treptozotocin-induced diabetes was also settled one year later by Kandeel et al [ 113 ].…”
Section: Zno Nanoplatforms For Diabetes Treatmentmentioning
confidence: 99%
“…Measurement of lipid peroxidation is a golden marker of oxidative damage caused by ROS, and the assessment of MDA is a reliable method to gain such determination [30]. It was observed that the level of MDA was increased time and concentration dependently.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that following treatment of Leishmania major promastigotes with ZnO nanoparticles, necrotic and apoptotic effects in the parasite were emerged [16]. It is well documented that metal oxide nanoparticles release ROS in huge amount and thereby exert their cytotoxic effects [1,30]. Taking together it can be concluded that ZnO and FeO nanoparticles exert their anthelmintic effects via induction of oxidative/nitrosative stress.…”
Section: Discussionmentioning
confidence: 99%